Summary of the 2015 University of Michigan Sport Concussion Summit. (23rd September 2016) - Broglio, Steven P; Baldwin, Grant; Castellani, Rudy J; Chrisman, Sara PD; Duma, Stefan; Hainline, Brian; Gerstner, Joanne C; Guskiewicz, Kevin; Kutcher, Jeffrey; Lamba, Adria; McCrea, Michael; Pachman, Steven; et al.
Discussions surrounding concussion have made their way into the public sphere over the previous decade with media attention and coverage of the injury fueling public debate. These conversations have devolved into discussions on banning contact and collision sports and raised legal questions surrounding injury management. Questions raised about concussion eclipse what science can answer, but the University of Michigan Injury Center (MI, USA) hosted a Concussion Summit in September 2015 as a means to condense, solidify and disseminate what is currently known on the topic. Areas for discussion included concussion incidence and prevention, diagnosis and management, legislation and education, legal and social aspects and future directions. A summary of those presentations are included within.